Financial Performance of Tourism Companies in Romania - Lőrincz, Annamária (Acta Carolus Robertus, 2025)
The study presents and analyses the performance of NACE 5510 (Hotels and other accommodation services) for the period of 2018-2022. Due to the specificities of the sector, the measurement can be done from several perspectives, in this research we will first look at the sector-specific indicators, followed by the financial analysis. In real terms, the sector will have caught up with 2018 in terms of turnover by 2022, but will not have yet reached 2019 levels, as can be forecasted on the basis of the number of overnight stays. This result is due to the importance of domestic tourism.Due to the inhomogeneity identified in the basic statistical analysis, the companies’ financial analysis is discussed at cluster level, using the EMIS database (N=791). Clusters are based on five-year averages of ROA, ROE, ROS profitability ratios. The results distinguish seven clusters that are statistically significantly different (Kruskal-Wallis test), which can be classified into three groups based on pairwise comparisons (Dunn test) as good, medium and relatively poor performers.
Keywords: pénzügyi teljesítmény; klaszterelemzés; turizmus; szálláshelyek; Románia